Pengaruh Lama Fermentasi dan Takaran Bahan Pembuatan Pupuk Organik Cair Turi (Sesbania Grandiflora L) Terhadap Kandungan Bahan Organik - Yeri Yeri; Darwati Susilastuti; Aditiameri Aditiameri (Fakultas Pertanian Universitas Borobudur, 2024)
In this study, the research aimed to determine the optimal combination of fermentation duration and material dosage for making turi liquid organic fertilizer. The study was conducted at the Laboratory of the Faculty of Agriculture, Borobudur University, and further tested at the Laboratory of the Department of Soil Science and Land Resources, Bogor Agricultural Institute. The research compared different combinations of fermentation duration and material dosage using five parameters: C-Organic, pH, N, P, and K. The results showed that the best combination was a fermentation time of 7 days with a 1:1 material dosage of turi leaf to brown sugar. This combination had a higher organic content compared to a fermentation time of 7 days with a 2:1 material dosage. Additionally, a fermentation time of 10 days with a 2:1 material dosage had a higher organic matter content compared to a 1:1 material dosage. Overall, a fermentation time of 7 days and a 1:1 material dosage were found to be the best for making turi leaf organic fertilizer